Seasonal Minimum and Maximum Solar Ultraviolet Exposure Measurements of Classroom Teachers Residing in Tropical North Queensland, Australia. (27th February 2019) - Downs, Nathan J.; Igoe, Damien P.; Parisi, Alfio V.; Taylor, Olivia; Lazzaroni, Shari L.; Rawlings, Alex; Garzón‐Chavez, Daniel R.; Harrison, Simone L.
Abstract: The risk of keratinocyte skin cancer, malignant melanoma and ultraviolet radiation (UVR)‐induced eye disease is disproportionately higher in Australia and New Zealand compared to equivalent northern hemisphere latitudes. While many teachers are aware of the importance of reinforcing sun safety messages to students, many may not be aware of the considerable personal exposure risk while performing outdoor duties in locations experiencing high to extreme ambient UVR year‐round. Personal erythemally effective exposure of classroom teachers in tropical Townsville (19.3°S) was measured to establish seasonal extremes in exposure behavior. Mean daily personal exposure was higher in winter (91.2 J m ‐2, 0.91 Standard Erythema Dose [SED]) than summer (63.3 J m −2, 0.63 SED). The range of exposures represents personal exposures that approximate current national guidelines for Australian workers at the study latitude of approximately 1.2 SED (30 J m −2 effective to the International Commission on Non‐Ionizing Radiation Protection). Similar proportions of teachers spent more than 1 h outdoors per day in winter (28.6%) and summer (23.6%) as part of their teaching duties with seasonal differences having little effect on the time of exposure. Personal exposures for teachers peaked during both seasons near school meal break times at 11:00 am and 1:00 pm, respectively. Abstract : Personal erythemally effective exposure of classroom teachers in tropical Townsville (19.3°S) was measured to establish seasonal extremes in exposure behavior. Mean daily personal exposure was higher in winter (91.2 J m ‐2, 0.91 Standard Erythema Dose [SED]) than summer (63.3 J m −2, 0.63 SED). The range of exposures represent personal exposures that approximate current national guidelines for Australian workers at the study latitude of approximately 1.2 SED (30 J m −2 effective to the International Commission on Non‐Ionizing Radiation Protection).